Study of wind loads on rectangular plan tall building under interference condition. (September 2022) - Chauhan, Bharat Singh; Chakrabarti, Anupam; Ahuja, Ashok Kumar
Abstract: The change in distribution of wind pressure due to alteration of wind flow pattern caused by the existence of an interfering building is explored in this study on a principal tall building having cross-section of rectangular shape. Interfering building having same cross-sectional shape as the principal building but a variation in height is placed in-front of the principal building, with across-wind lengths of two buildings being in-line with each other. Keeping the principal building fixed in position, the spacing between two buildings is varied by changing the position of interfering building, so as to understand the effect of spacing and height variation upon the wind loads and pressures. Two independent type of measurements are undertaken for varying interfering building height: (1). Force Measurement (2). Pressure Measurement. For purpose of validation, the results obtained from two independent measurements mentioned are compared later. The results obtained from force measurements are expressed in the form of two-dimensional X-Y plots, while that for pressure measurement are depicted in the form of mean and RMS wind pressure coefficient ( C P and C P ' ) contour plots on all vertical faces of the principal building. Force measurement results show that the interference effect subsides as the interfering building height is reduced and spacing is increased. However, from pressure contours it is evident that when the interfering building is close to principal building pressure force on the windward face reduces while the suction on the leeward face increases with the reduction in interfering building height. Negative drag is also observed for few of the cases.